The Relationship between Initiative Taking Levels and Problem Solving Skills of School Administrators - Uğur Akın; Tarık Tekin (Anadolu Üniversitesi Eğitim Fakültesi dergisi)
This research aims to examine the relationship between initiative taking levels and problem solving skills of school administrators. The research was designed as a descriptive relational survey. The sample consists of 282 preschool, primary, secondary and high school administrators working in public schools from a central Black Sea Region province of Turkey. Data were collected through the Personal Initiative Measurement Tool for School Principals and the Problem Solving Inventory. Relationships were tested through Pearson’s correlation and multiple linear regression analyses. Results indicated that there were negative significant relationships between the impulsive and avoidant problem solving styles and all sub-dimensions of taking initiative, while the relationships were significant and positive for reflective style, problem solving confidence, monitoring, and planfulness. Multiple linear regression analyses showed that the most powerful predictor of school administrators’ taking initiative was the problem solving confidence. It was concluded that supporting school principals for effective problem solving skills may increase their level of taking initiative.